A Novel Method for Gas Generation Law Calculation of Fractured Propellant Charge. Issue 9 (25th July 2018) - Li, Chao; Rui, Xiaoting; Wang, Yan; Zhao, Xin
Abstract: Aimed at the problem that the gas generation law of fractured propellant charge cannot be calculated by geometry method accurately due to various shapes and sizes of fractured propellant charge, a method for calculating the equivalent form function of fractured propellant charge based on the initial dynamic vivacity ratio theory is proposed. The equivalent form functions of propellant charge with different fracture degrees are deduced from this method on the basis of the initial dynamic vivacity ratio test results. Based on the equivalent form functions of propellant charge with different fracture degrees, the relationship between the maximum bore pressure in tank gun and the initial dynamic vivacity ratio of the fractured propellant charge at the bottom of projectile is established, which lays a theoretical foundation for the criteria of propellant charge launch safety. Abstract :